Flos Puerariae-Semen Hoveniae medicinal pair extract ameliorates DSS-induced inflammatory bowel disease through regulating MAPK signaling and modulating gut microbiota composition - Xiaofan Chen; Xiaofan Chen; Jiahui Zhang; Rui Li; Hua Zhang; Yong Sun; Li Jiang; Xiaoya Wang; Yaokun Xiong (Frontiers Media S.A., 2022)
Background: Inflammatory bowel disease (IBD) is a global gastrointestinal disease characterized by relapsing and remitting inflammatory conditions. Flos Puerariae (the flower of Pueraria lobata [Willd.] Ohwi and P. thomsonii Benth.) and Hovenia dulcis Thunb. (Rhamnaceae) are traditional Chinese medicines. This medicinal pair has been used to treat various diseases due to its excellent anti-oxidant and anti-inflammatory activity. However, the effects of extracts from these plants on dextran sulfate sodium (DSS)-induced colitis have not been investigated; further study is needed to improve the understanding of their mechanisms of action and potential applications.Methods: The chemical constitution of extracts from Flos Puerariae and Semen Hoveniae (PHE) was analyzed using UPLC-LTQ-Orbitrap-MS/MS. The protective effects of PHE on mice with DSS-induced colitis were evaluated through assessment of body weight loss, disease activity index (DAI) score, colon length shortening, and pathological changes. The levels of inflammatory cytokines were determined by ELISA and RT-qPCR. Biomarkers of oxidative stress (ROS, CAT, SOD, MDA, and T-AOC) were analyzed using biochemical kits. The expression of MAPK proteins was determined by Western blotting analysis. Gut microbiota were analyzed via 16S rRNA sequencing.Results: Chemical composition analysis indicated that PHE contains various bioactive compounds, including puerarin, kakkalide, tectoridin, and genistin. The findings from this study suggest that PHE could effectively modulate histopathological score, inflammatory cell infiltration, and inflammatory factor secretion. Notably, PHE ameliorated oxidative stress by inhibiting activation of the MAPK pathway, leading to decreased inflammatory mediators and restored antioxidant enzyme activity. Furthermore, PHE treatment regulated the composition of the gut microbiota by increasing the abundance of benign bacteria, such as Akkermansia, and reducing the abundance of harmful bacteria, such as Proteobacteria.Conclusion: The findings from this study demonstrate the mechanism underlying the amelioration of DSS-induced intestinal oxidative stress by PHE and its positive impact on the restoration of the composition of gut microbiota.